[PP.30.09] DOSE SALT INTAKE PREDICT THE NEW ONSET OF CHRONIC KIDNEY DISEASE?. (September 2016) - Takase, H.; Tanaka, T.; Nonaka, D.; Takayama, S.; Hayashi, H.; Sugiura, T.; Ohte, N.; Dohi, Y.
Abstract : Objective: Dietary salt, which is one of the most important modifiable factors in our life style, is associated not only with blood pressure but also with several cardiovascular diseases in a blood pressure–independent manner. We investigated if salt intake predicts new onset of chronic kidney disease (CKD) in the general population. Design and method: Consecutive 8, 161 participants (male = 5, 168, 55.8 ± 11.3 year-old) with normal estimated glomerular filtration rate (eGFR;> = 60 ml/min/1.73 m 2 ) in our physical health check-up program were enrolled in this study. After baseline examination, participants were followed up (median 1, 098 day) with the endpoint being the development of CKD (eGFR<60 ml/min/1.73 m 2 ). Individual salt intake was estimated using spot urine by a previously reported method and GFR was estimated using the Japanese Society of Nephrology formula. Results: Salt intake was 8.9 ± 2.0 g/day in male and 8.6 ± 1.9 g/day in female subjects. eGFR was 80.1 ± 12.7 ml/min/1.73 m 2 at baseline, and during the follow-up period, CKD developed in 706 subjects (29.9 per 1000 person-year), with the incidence being more frequent in male than female subjects (31.1 vs. 27.8 per 1000 person-year). Non-adjusted hazard ratio (HR) (95% confidence interval [CI]) of salt intake for the new CKD was 1.071 (1.034–1.109). Multivariate Cox-hazard analysis adjusted for body mass index, systolic blood pressure, heart rate, uric acid, fasting plasma glucose, low-density lipoprotein cholesterol, triglyceride, hemoglobin, smoking status and eGFR at baseline demonstrated that salt intake was a significant predictor of new onset CKD (HR = 1.077, 95%CI = 1.037–1.119). Univariate and adjusted multivariate liner regression analyses indicated the significant correlation between salt intake at baseline and yearly changes in eGFR (r = -0.081, p < 0.001 and r = -0.069, p < 0.001, respectively). Similar results were obtained in a sub-analysis performed in subjects with normal blood pressure (n = 5, 863). Conclusions: Dietary salt intake is significantly associated with the development of CKD and decrease in eGFR in the general population, even in normotensive subjects. These results suggest that salt restriction is beneficial for the prevention of the impairment of kidney function and the development of CKD.